2017
DOI: 10.1017/s2045796016001074
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of psychotic and affective symptoms in Rwandan and Kenyan students

Abstract: Aims. War and conflict are known to adversely affect mental health, although their effects on risk symptoms for psychosis development in youth in various parts of the world are unclear. The Rwandan genocide of 1994 and Civil War had widespread effects on the population. Despite this, there has been no significant research on psychosis risk in Rwanda. Our goal in the present study was to investigate the potential effects of genocide and war in two ways: by comparing Rwandan youth born before and after the genoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…In addition, the pooled prevalence of PEs in students from Western countries was 29.60%, which was significantly higher than that reported by students from Eastern countries. These findings provide support to the very limited evidence available in non‐student samples claiming that prevalence and nature of PEs vary across countries 28,79 . Indeed, although prevalence of psychotic disorders does not differ across cultures, 80 psychotic manifestations and symptoms, as well as their subsequent levels of distress have been found to be culturally dependent 81–83 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, the pooled prevalence of PEs in students from Western countries was 29.60%, which was significantly higher than that reported by students from Eastern countries. These findings provide support to the very limited evidence available in non‐student samples claiming that prevalence and nature of PEs vary across countries 28,79 . Indeed, although prevalence of psychotic disorders does not differ across cultures, 80 psychotic manifestations and symptoms, as well as their subsequent levels of distress have been found to be culturally dependent 81–83 .…”
Section: Discussionsupporting
confidence: 75%
“…These findings provide support to the very limited evidence available in non-student samples claiming that prevalence and nature of PEs vary across countries. 28,79 Indeed, although prevalence of psychotic disorders does not differ across cultures, 80 psychotic manifestations and symptoms, as well as their subsequent levels of distress have been found to be culturally dependent. [81][82][83] In a cross-cultural comparative study, Vermeiden et al found that students from a non-Western developing country (i.e., Nigeria) had significantly more frequent and distressing PEs than students from developed Western countries (i.e., the Netherlands and Norway).…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistencies could be due to the observation that PLEs are normative in development and, therefore, could be experienced by both genders at the same or different magnitude (Mamah et al, 2012). The finding, therefore, raises the possibility that both males and females were exposed to the same or similar risk factors of PLEs, such as malnutrition, child labour, child maltreatment and abuse that are reportedly common in Ghana and other African countries at the same or similar magnitude (Adjorlolo et al, 2017;Mamah et al, 2016;Okewole et al, 2015;Owoso et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, the existing studies from South Africa and Kenya have also examined different facets of psychosis, therefore making the results difficult to compare. For example, studies from Kenya focused predominantly on the cultural appropriateness and usefulness of psychosis screening measures, as well as prevalence of psychosis in non-clinical samples (Mamah et al, 2012(Mamah et al, , 2016(Mamah et al, , 2013(Mamah et al, , 2014Owoso et al, 2018Owoso et al, , 2014, as opposed to the demographic and clinical profiling of individuals diagnosed with psychosis in South Africa (Paruk et al, 2013(Paruk et al, , 2015(Paruk et al, , 2017(Paruk et al, , 2018(Paruk et al, , 2009. This review has largely corroborated early suggestion that mental health in general (Charlson et al, 2014;Cortina et al, 2012;Sipsma et al, 2013) and mental health research in particular (Sankoh et al, 2018;Ssewamala et al, 2018) has been granted scant attention in Africa for reasons such budgetary constraints (Chisholm et al, 2019) and limited human resource (Cortina et al, 2012;Roberts et al, 2014;Sankoh et al, 2018).…”
Section: Discussionmentioning
confidence: 64%
“…The evidence on the nexus between adversities and psychosis from high income countries (Davies et al, 2020;Oliver et al, 2020;Rodrigues & Anderson, 2017) provides suitable justification for research on psychosis in a continent riddled with adverse environmental factors. Notable among them are malnutrition, child labor, child maltreatment and abuse, physical conditions such as HIV, violence/war/conflict (Owoso et al, 2018), traumatic brain injury, poor antenatal/obstetric history (Okewole et al, 2016), childhood developmental abnormalities and early infections (Messias et al, 2007). Current developments, indeed, suggest that there is a growing interest to establish a research agenda in psychosis in Africa to support evidencebased, culturally sensitive decision-making and discussions bothering the detection/assessment and prevention of psychosis through public health intervention problems.…”
Section: Introductionmentioning
confidence: 99%